Aesthetic rehabilitation with multiple loop connectors - Ashish Kalra; Mahesh E Gowda; Kamal Verma (Wolters Kluwer Medknow Publications, 2013)
Patients with a missing tooth along with diastema have limited treatment options to restore the edentulous space. The use of a conventional fixed partial denture (FPD) to replace the missing tooth may result in too wide anterior teeth leading to poor esthetics. The diastema resulting from the missing central incisors can be managed with implant-supported prosthesis or FPD with loop connectors. An old lady reported with chief complaints of missing upper anterior teeth due to trauma. Her past dental history revealed that she was having generalized spacing between her upper anterior teeth. Considering her esthetic requirement of maintaining the diastema between 12, 11, 22, and 21, the treatment option of 06 units porcelain fused to metal FPD from canine to canine with intermittent loop connectors between 21, 22, 11, 12 was planned. Connectors basically link different parts of FPDs. The modified FPD with loop connectors enhanced the natural appearance of the restoration, maintained the diastemas and the proper emergence profile, and preserve the remaining tooth structure of abutment teeth. This clinical report discussed a method for fabrication of a modified FPD with loop connectors to restore the wide span created by missing central incisors.